NATIONAL LITERATURE AS A MEANS OF DEVELOPMENT THE GENERAL CULTURAL COMPETENCE OF FUTURE SPECIALISTS: PERSONALISTIC CONTEKST - Dr. Halyna Vasylivna Bilavych,; Fedchyshyn, Nadiia Orestivna; Rozman, Iryna Illivna; Vysochan, Lesia Mykhaylivna; Savchuk, Dr. Borys Petrovych; Bahriy, Mariya Antonivna; Kononenko, Iryna Vitaliivna; Yuriyivna, Vysochan Zoryana (International Journal of Psychosocial Rehabilitation, 2020)
Today, students are losing interest in reading, considering it just waste of time. They rarely visit theater, artistic exhibitions, and show little interest in classical music. The Internet, social networks, cinema etc. have pushed out the arts from the sphere of cultural interests of young people. So, according to our respondents, literature as one of the genres of art ranks third, being inferior to cinema and music. And such arts as decorative crafts, opera, circus, ballet, symphony music, painting, sculpture, architecture, choreography occupy the last positions. This situation is worrying because such means of raising spirituality, the general cultural level, intelligence, as literature and art (all its genres) lose their educational effect. She requires the development of a strategy for the formation of the general cultural level of future intellectuals. In our opinion, the first step on this path should be to use the potential of literature, including the regional literature. National (regional) fiction can become a powerful means of stimulating the reading interests of students, i.e. it can become that particular initial stage that will encourage them to get further deeper knowledge of culture and arts.